2016
DOI: 10.5114/jcb.2016.60452
|View full text |Cite
|
Sign up to set email alerts
|

Focal partial salvage low-dose-rate brachytherapy for local recurrent prostate cancer after permanent prostate brachytherapy with a review of the literature

Abstract: PurposeTo investigate the treatment results for focal partial salvage re-implantation against local recurrence after permanent prostate brachytherapy.Material and methodsBetween January 2010 and September 2015, 12 patients were treated with focal partial salvage re-implantation for local recurrence after low-dose-rate brachytherapy using 125I seeds. The focal clinical target volume (F-CTV) was delineated on positive biopsy areas in a mapping biopsy, combining the cold spots on the post-implant dosimetry for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 25 publications
0
20
1
Order By: Relevance
“…We observed slightly better outcomes regarding treatment related toxicities than that reported in both EBRT and brachytherapy series [26, 27, 28], which could be explained by the use of the real time MRI/TRUS fusion protocol. All patients in our study showed an appropriate biochemical response; with PSA nadir of 0.73 ng/ml (range: 0.1-3.89 ng/ml) at last follow-up visit, being the median pretreatment PSA 2.71 ng/ml (range: 1.84-13.93 ng/ml).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…We observed slightly better outcomes regarding treatment related toxicities than that reported in both EBRT and brachytherapy series [26, 27, 28], which could be explained by the use of the real time MRI/TRUS fusion protocol. All patients in our study showed an appropriate biochemical response; with PSA nadir of 0.73 ng/ml (range: 0.1-3.89 ng/ml) at last follow-up visit, being the median pretreatment PSA 2.71 ng/ml (range: 1.84-13.93 ng/ml).…”
Section: Discussioncontrasting
confidence: 51%
“…Although there are some studies investigating the role of brachytherapy for local recurrences after prostate radiotherapy or brachytherapy [27, 28], very few series have reported results of salvage brachytherapy after radical prostatectomy and the number of patients included is rather small [27, 28, 29, 30, 31, 32, 33, 34, 35, 36]. Table 3 shows a description of these series.…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the potential utility of mpMRI as a diagnostic strategy to guide biopsy if local salvage options are considered. The increasing interest in the use of focal therapies or focal salvage approaches (23)(24)(25)(26) necessitates a clear understanding of sites of recurrence to maximize efficacy. Further, the patterns of recurrence may have implications for the treatment of patients with brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, focal salvage is still in the experimental phase, as is reflected in the amount of literature available on the subject. This is especially clear in the 125 I brachytherapy setting, in which only four studies so far were published (with 12, 15, 20, and 25 patients, respectively) [17, 19, 31, 32]. The effect of focal salvage regarding biochemical control and prostate cancer specific survival in the long run is still unknown, since multifocal disease might be present at the time of failure and subsequently during salvage treatment.…”
Section: Discussionmentioning
confidence: 99%